Solid contact sensors for determination of the antihistaminic drug ketotifen fumarate - Issa, Yousry M.; Khater, Motaza M.; Mohamed, Sabrein H. (Univerzita Pardubice, 2012)
Reliable potentiometric sensing devices with unique advantages were constructed for determination of ketotifen fumarate (keto-fuma). Five sensors based on Ag, Ag/Ag2S, Ag/AgCl, graphite and glassy carbon solid beds were constructed. These sensors were constructed based on ketotifen-tetraphenylborate (keto-TPB) as ion pairing material and dibutyl phthalate as solvent mediators. The sensors showed high sensitivity and near Nernstian slope in batch and flow injection conditions (FIA). According to the results obtained, the best behavior observed for coated graphite sensor was with slope 60.10 mV·decade–1, linear range 7×10–6–1×10–2 M, and limit of detection 3.9×10–7 M. Enhancement of the detection limit of the sensors was done by incorporating potassium tetraphenylborate (KTPB) and graphite in the membrane. The sensors were used for determination of keto-fuma in the pure form as well as in its pharmaceutical preparations. It was performed using potentiometric titration and standard addition methods with recoveries of 97.0–100.4 % and relative standard deviations of 0.13–1.42 %.
Keywords: ketotifen fumarate; sensors; graphite; solid contact